Comparison of alveolar ridge splitting and autogenous onlay bone grafting to enable implant placement in patients with atrophic jaw bones - GARİP, HASAN (SAUDI MED J, 2017)
Objective: To compare alveolar ridge splitting (ARS) and autogenous onlay bone grafting (AOBG) in atrophic jaw bones. Methods: Forty patients were included in this retrospective, parallel-group study conducted at the Istanbul Medipol University School of Dentistry, Istanbul, Turkey, between 2012-2015. The initial bone thickness was measured by cone beam computed tomography (CBCT). Patients were allocated into ARS (n=17) and AOGB (n=23) groups on the basis of ridge thickness and shape. Follow-up CBCT measurements to assess horizontal bone were repeated 4 to 6 months post augmentation. The diameters of the implants were recorded. Implant bone resorption was measured at one year post implant placement on panoramic radiography. Surgical complications and implant survival were evaluated. Results: The final bone width in the AOBG group was significantly higher than that in the ARS group (p=0.029). Forty-four implants were inserted in the AOGB group, whereas 33 implants were inserted in the ARS group. There was no significant difference regarding implant diameter (p=0.920). Implant survival rate was 93.9% in the ARS group and 93.1% in the AOGB group. Peri-implant bone resorption at one year was higher in the AOBG group than in the ARS group (p=0.032). There were minor surgical complications, including bad split and wound dehiscence. Conclusion: The incidence of peri-implant bone resorption for the AOGB technique was higher than that for the ARS technique, but their implant survival rates were similar.
Keywords: AUGMENTATION PROCEDURES; BLOCK GRAFTS; RECONSTRUCTION; COMPLICATIONS; REGENERATION